PENGARUH MODAL USAHA DAN LAMA MELAUT, TERHADAP HARGA JUAL IKAN PADA PASAR TRADISIONAL SANGGENG MANOKWARI - Sarce Babra Awom (Cakrawala Management Business Journal, 2019)
The purpose of this study was to measure the effect of venture capital (X1) and the long time at sea /time work hours (X2) for the offer price of fish (Y) in the tradisional sanggeng market manokwari, with 73 respondents chosen randomly and consisted of sellers and buyers in the sanggeng market. Data collection methods are done through interviews, (primary data) with a questionnaire and then carried out a questionnaire test and test the quality of the data, and then analyzed uiple linear regression. The result of research simultan eously or statistically partial variables X1 (venture capital) and variable X2 (long sea) significantly influence the higt selling price of fish (variable y) in the manokwari sanggeng market because the value of p. Value (0,000)<(0.05) sig (5%.) so it can be concluded that when fish traders increase capital by 1% the price of fish in the market rises by 13,5% and also when a long time to go to sea increases 1 day than the price of fish increases by 33.900,00. The government needs to control high (expensive) fish prices in the market by activating an inflation control team that continues to monitor the market price (specifically) of the fisheries sector.